Higher-order thinking skills (HOTS) in reading comprehension of EFL class - Farchan Fitro Akbar; Eka Wilany; Safnidar Siahaan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
Higher Order Thinking Skills (HOTS) have become a crucial focus in EFL classrooms, especially in reading comprehension, as they support learners in developing critical, analytical, and reflective skills. This study aimed to explore students’ perceptions of HOTS implementation in reading activities and assess their HOTS-based reading comprehension abilities. This qualitative descriptive involved one EFL class at Riau Kepulauan University who had completed the Extensive Reading course. Data collection employed a questionnaire assessing four HOTS indicators, such as creative thinking, critical thinking, problem solving, and decision making, and a reading comprehension test focusing on three HOTS components, consist of critical thinking, transfer, and problem solving. The results showed that most students had positive perceptions, with dominant responses falling into "Agree" and "Neutral" categories across all indicators. In the reading test, the majority of students demonstrated strong performance, 65–88% showed high-level critical thinking, 81–85% performed well in transfer tasks, and 73–77% successfully solved problems by designing logical endings and action plans. These findings suggest that integrating HOTS into reading instruction fosters cognitive growth and engagement. It is therefore recommended that educators incorporate HOTS-based strategies more systematically, providing structured activities and continuous support to enhance students’ higher-order thinking in EFL reading contexts.